2018
DOI: 10.1111/apt.14487
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of ustekinumab in 122 refractory Crohn's disease patients: a multicentre experience

Abstract: In this cohort of refractory CD patients receiving long-term ustekinumab therapy, more than 50% of patients continued ustekinumab treatment with no loss of response, intolerance or surgery and with a good safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 23 publications
10
93
1
Order By: Relevance
“…Ustekinumab induction treatment using a subcutaneous preparation has already been approved for the treatment of moderate‐severe plaque psoriasis. Subcutaneous ustekinumab has been used off‐label in the treatment of Crohn's disease, with long‐term outcomes reported in various cohorts . We report outcomes with a subcutaneous induction regimen for Crohn's Disease with a cumulative dose of 360 mg ustekinumab, given in 3 divided subcutaneous doses, of 180 mg at Week 0 and 90 mg at Week 1 and Week 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab induction treatment using a subcutaneous preparation has already been approved for the treatment of moderate‐severe plaque psoriasis. Subcutaneous ustekinumab has been used off‐label in the treatment of Crohn's disease, with long‐term outcomes reported in various cohorts . We report outcomes with a subcutaneous induction regimen for Crohn's Disease with a cumulative dose of 360 mg ustekinumab, given in 3 divided subcutaneous doses, of 180 mg at Week 0 and 90 mg at Week 1 and Week 2.…”
Section: Discussionmentioning
confidence: 99%
“…1 Emergency surgery increased the risk of early post-operative complications, odds ratio 4.46 (95% confidence interval 1.75-11.36), and similar findings regarding emergency surgery has been shown previoulsy. [5][6][7] An English study on emergency colorectal surgery 5 found the 30-day mortality risk to be four-times greater compared with scheduled procedures. 8 Similar to Sacleux et al, 3 they found UC to be associated with more complications than CD.…”
Section: Editorial: Post-operative Complications In Elderly Onset Infmentioning
confidence: 99%
“…Gastroenterologists and surgeons must work together to prevent unnecessarily high rates of emergency surgery, 43.9% in CD and 36.5% in UC. 6 Although I may be biased by being a surgeon, I am far from convinced that this should be interpreted as a factor against surgery among elderly IBD patients when needed. Rather, I think this shows even more firmly that we need to discuss these patients in multi-disciplinary team meetings INVITED EDITORIALS | 383…”
Section: Editorial: Post-operative Complications In Elderly Onset Infmentioning
confidence: 99%
See 2 more Smart Citations